Comparison of Law Between Merariq Traditional Marriage Law and Marriage Law Number 16 of 2019 - Rully Syahrul Mucharom; Wardah Yuspin; Absori (Proceeding International Conference Restructuring and Transforming Law, 2022)
Marriage Law in Indonesia is regulated in Act Number 1 of 1974 concerning Marriage and undergoing changes to Act Number 16 of 2019, which regulates how the norms and principles of marriage are considered and recognized by the Indonesian state. The purpose of marriage in Indonesia as regulated in Act Number 1 of 1974 article 1 states that: "Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the Almighty God. one". The problem that arises then is whether the existing and developing customary marriages before the enactment of the Marriage Law can be recognized by the Indonesian state. The types of customary marriages that are not in accordance with the objectives, norms, and principles of marriage according to the Marriage Law are one of them is the Merariq Traditional Marriage Tradition, which from this merariq marriage tradition results in many early marriages or child marriages according to the legal age threshold. Law Number 16 of 2019 which is the main discourse of this study looks at the dimensions of Marriage Law through the eyes of the Merariq Indigenous Marriage of the Sasak Tribe. This study uses a normative juridical approach where this approach is carried out by tracing the norms that live in Indonesian positive law. Whereas the cases raised by merariq traditional marriages have caused many legal problems, furthermore, the high level of child marriage is due to the absence of a social safety net for anyone who wants to carry out a merariq marriage so that there is no legal protection and certainty for the parties to the marriage, especially women who are in a vulnerable position, Therefore, the implementation and enforcement of national marriage law must be considered again in its enforcement and implementation so that there is no legal vacuum where national law is not present in the community.